Characterization of soot inside a diesel particulate filter during a nonthermal plasma promoted regeneration step. (5th March 2019) - Shi, Yunxi; Cai, Yixi; Fan, Runlin; Cui, Yingxin; Chen, Yi; Ji, Liang
Graphical abstract: Highlights: DPF low temperature regeneration assisted by NTP technology has been tested. The particle sediments and the corresponding DPF channel wall were sampled as a whole. The soot cake changed from a stratified structure to a dispersed block structure. The pyrolysis characteristic temperatures of EC in PM were lowered significantly. NTP has the ability to improve the oxidation activity of PM. Abstract: Nonthermal plasma can achieve diesel particulate filter regeneration under much lower temperatures (≤200 °C), showing promise for potential applications. To investigate the evolution of particulate matter, partial regeneration of a filter was produced by active substances generated by a plasma injection system. The surface morphology, oxidation characteristics, and surface functional groups of particle samples inside the filters before and after regeneration were investigated using digital electron microscopy, scanning electron microscopy, thermal gravimetric analysis, and fourier transform infrared spectrometry. Results show that during the regeneration step, the soot cake surface changed from random irregular cracks to more uniform and relatively dense pores. Decreases in characteristic temperatures and the growth of oxygen-containing functional groups indicated that nonthermal plasma could improve the oxidizing activity of particulate matter. The reaction between nonthermal plasma and particulate matter was most intense but not limited to the regeneration interface area of the soot cake.